Pelatihan Penyusunan Laporan Keuangan Dengan Menggunakan Ms. Excel Bagi Pengurus Koperasi di Di. Yogyakarta - Keri Boru Hotang; Eindye Taufik (Universitas Muria Kudus, 2023)
Cooperatives are legal entities established by individuals or legal entities. Lack of understanding and knowledge of management cooperative about system good financial administration on cooperatives, and the impoertance of financial statements that can be a consideration for the community in assessing cooperative performace. This community service method is (1) lectures and (2) computer practice. The result; provides the benefits of knowledge for participants about good and correct cooperative financial management, as well as how to make financial reports quicly by applying the Ms. excel.